Metabolic engineering of a xylose pathway for biotechnological production of glycolate in Escherichia coli - Liu, Min (Microb Cell Fact, 2018)
BACKGROUND: Glycolate is a valuable chemical with extensive applications in many different fields. The traditional methods to synthesize glycolate are quite expensive and toxic. So, the biotechnological production of glycolate from sustainable feedstocks is of interest for its potential economic and environmental advantages. d-Xylose is the second most abundant sugar in nature and accounts for 18–30% of sugar in lignocellulose. New routes for the conversion of xylose to glycolate were explored. RESULTS: Overexpression of aceA and ghrA and deletion of aceB in Escherichia coli were examined for glycolate production from xylose, but the conversion was initially ineffective. Then, a new route for glycolate production was established in E. coli by introducing NAD(+)-dependent xylose dehydrogenase (xdh) and xylonolactonase (xylC) from Caulobacter crescentus. The constructed engineered strain Q2562 produced 28.82 ± 0.56 g/L glycolate from xylose with 0.60 ± 0.01 g/L/h productivity and 0.38 ± 0.07 g/g xylose yield. However, 27.18 ± 2.13 g/L acetate was accumulated after fermentation. Deletions of iclR and ackA were used to overcome the acetate excretion. An ackA knockout resulted in about 66% decrease in acetate formation. The final engineered strain Q2742 produced 43.60 ± 1.22 g/L glycolate, with 0.91 ± 0.02 g/L/h productivity and 0.46 ± 0.03 g/g xylose yield. CONCLUSIONS: A new route for glycolate production from xylose was established, and an engineered strain Q2742 was constructed from this new explored pathway. The engineering strain showed the highest reported productivity of glycolate to date. This research opened up a new prospect for bio-refinery of xylose and an alternative choice for industrial production of glycolate.